2022
DOI: 10.3390/buildings12020100
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Response of Novel Layered Geopolymer Fibrous Concrete to Drop Weight Impact

Abstract: In recent years, geopolymer concrete (GC) has become more popular in construction because of its multiple benefits, such as eco-friendliness, high temperature resistance and resistance to chemical attack in harsh environments. However, GC has limited deformation capability and tensile strength compared to ordinary concrete. Geopolymer fibrous concrete (GFC) exhibits high mechanical properties, such as compressive strength and impact strength. This study aimed to develop a novel composite comprising GFC at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Asphalt-coated aggregate added to concrete did not affect the brittle failure mode. Non-fibrous cylindrical specimens were commonly subjected to this form of brittle failure, as reported in the scientific literature [ 10 , 52 ]. As a result of concrete’s heterogeneity and brittleness and the absence of any bridging elements, this behaviour was observed.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Asphalt-coated aggregate added to concrete did not affect the brittle failure mode. Non-fibrous cylindrical specimens were commonly subjected to this form of brittle failure, as reported in the scientific literature [ 10 , 52 ]. As a result of concrete’s heterogeneity and brittleness and the absence of any bridging elements, this behaviour was observed.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In Murali et al's other work [10] in this Special Issue, a novel composite comprising geopolymer fibrous concrete (GFC) at the tension zone and geopolymer concrete (GC) at the compression zone was developed. The results indicated that the impact strength of GFC was significantly improved in long steel fiber-based specimens.…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…The incorporation of hybrid fibres on the ductility and impact resistance of GGBS-based GPC was studied and it was concluded that the ductility index was enhanced efficiently [ 48 , 49 , 50 ]. The impact resistance of GPC was also improved significantly with the introduction of fibres in mono and hybrid forms, changing the mode of failure from brittle to ductile [ 51 ].…”
Section: Introductionmentioning
confidence: 99%